2021
DOI: 10.1186/s42358-021-00192-6
|View full text |Cite
|
Sign up to set email alerts
|

Dualities of the vitamin D in systemic sclerosis: a systematic literature review

Abstract: Background Systemic sclerosis (SSc) is a chronic disease characterized by autoimmunity, vasculopathy, and visceral and cutaneous fibrosis. Vitamin D has several functions in the immunological system, and different studies have suggested a potential role in triggering autoimmune diseases. Patients with SSc may present with low serum levels of vitamin D, but the association between hypovitaminosis D and disease onset or any clinical manifestation is still obscure. Our goal was to verify the causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
1
6
1
1
Order By: Relevance
“…Vitamin D deficiency in SSc has been widely reported [17][18][19][20][21]. In the population studied, its prevalence reached 50%, and the association between vitamin D deficiency and a higher prevalence of arterial hypertension was one of the strongest findings in this study.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Vitamin D deficiency in SSc has been widely reported [17][18][19][20][21]. In the population studied, its prevalence reached 50%, and the association between vitamin D deficiency and a higher prevalence of arterial hypertension was one of the strongest findings in this study.…”
Section: Discussionsupporting
confidence: 50%
“…However, the results have not yet been published. A recent systematic review on vitamin D deficiency in SSc confirmed that SSc patients frequently present vitamin D deficiency and that its levels inversely correlate with the disease severity [18]. However, it also emphasized the lack of evidence for the beneficial impact of vitamin D in SSc and highlighted a need for future trials and fundamental research.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased availability of serum 25-hydroxyvitamin D (25[OH]D) has been postulated to compromise immune cell synthesis of hormonal 1,25-dihydroxyvitamin D, leading to impaired innate immunity and over-exuberant inflammatory adaptive immunity. 42 Patients with SLE, 43 fibromyalgia, 20 SSc, 44 , 45 AS, 46 SS, 47 and psoriasis 48 demonstrate low vitamin D levels, which tend to correlate inversely with disease activity. In rheumatology, vitamin D supplementation is prescribed for the prevention of glucocorticoid-induced osteoporosis, the reduction of fracture-risk, 49 and the management of pain (mainly in fibromyalgia).…”
Section: High-hierarchy Evidence For the Efficacy Of Immunonutrition ...mentioning
confidence: 99%
“…At the same time, no association was observed between the polymorphisms studied and the clinical picture of SSc [ 70 ]. Thorough research on the clinical effects of vitamin D supplementation in SSc patients as well as the clarification of vitamin D commitment in SSc pathogenesis is still needed [ 71 ].…”
Section: Vitamin D Deficiency and Epigenetic Dysregulations In Autoim...mentioning
confidence: 99%